Stability of DNA in nucleosomes. - Bina, M (1980)
Heats of thermal denaturation of chromatin core particles and core particles with covalently crosslinked histones were measured by differential scanning calorimetry. The additional stabilization of the nucleoprotein complex by crosslinking is not reflected in the transition enthalpy. The contribution of protein denaturation to the total heat was estimated by comparison of core particles with core particle DNA in a high-salt solution. By taking into account the temperature dependence of the transition enthalpy of DNA, we conclude that the enthalpy change for denaturation of DNA in core particles is nearly the same as that for naked DNA in solution.